Thermochemical principles of the production of lightweight aggregates from waste coal bottom ash. Issue 1 (17th September 2020) - Balapour, Mohammad; Rao, Rathin; Garboczi, Edward J.; Spatari, Sabrina; Hsuan, Y. Grace; Billen, Pieter; Farnam, Yaghoob
Abstract: Manufacturing lightweight aggregate (LWA) (ie, porous ceramics) by means of a sintering technique requires a delicate balance among three conditions: (a) forming a sufficient amount of molten liquid phase during sintering, (b) reaching an appropriate viscosity for solid‐liquid suspension, and (c) emitting a sufficient amount of gas that can be entrapped by the liquid phase to form pores. This study evaluates these three conditions in the production of LWAs made from two types of waste coal bottom ash (low‐calcium and high‐calcium), and relates them to the formation of LWA pore structure. A thermochemical analytical approach, including thermodynamic modeling and the Browning viscosity model, was used to quantify the extent of the liquid phase and calculate its viscosity. In conjunction with thermochemical analysis, an experimental approach including quantitative x‐ray diffractometry, thermogravimetric analysis, and x‐ray computed tomography was also used to identify the candidate chemical compounds that contribute to gas emission during sintering and to evaluate the LWA pore structure. The results indicated that a mass fraction of at least 50% for the liquid phase is required for a successful entrapment of emitted gaseous phases during sintering. Larger pores were observed in the microstructure of LWA samples made using high‐calcium bottom ash in comparison to those made with low‐calcium bottom ash. This observation was mainly attributed to the high‐calcium samples forming liquid phases with lower viscosities and emitting higher amounts of gaseous phase during sintering than did the low‐calcium samples. It was found that the gaseous phase was generated by hematite reduction and anhydrite decomposition, which led to the release of O2 and SO2 .